1997
DOI: 10.1161/01.cir.95.7.1945
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Reduces Tachycardia-Induced Electrical Remodeling of the Atria

Abstract: Electrical remodeling of the atrium during rapid atrial pacing was significantly attenuated by verapamil. This suggests that electrical remodeling of the atrium is triggered by the high calcium influx during rapid atrial pacing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
160
1
9

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(174 citation statements)
references
References 68 publications
4
160
1
9
Order By: Relevance
“…3,10 The present study is the first to quantify in vivo subcellular Ca distribution during AF. After 3-minute pacing, mean total cytoplasmic Ca increased by 1.1 mmol/kg dry wt, which, given a total/free Ca ratio of Ϸ500:1, represents an increase of Ϸ550 nmol/L of free Ca.…”
Section: Subcellular Changes In Total Camentioning
confidence: 87%
See 1 more Smart Citation
“…3,10 The present study is the first to quantify in vivo subcellular Ca distribution during AF. After 3-minute pacing, mean total cytoplasmic Ca increased by 1.1 mmol/kg dry wt, which, given a total/free Ca ratio of Ϸ500:1, represents an increase of Ϸ550 nmol/L of free Ca.…”
Section: Subcellular Changes In Total Camentioning
confidence: 87%
“…Calcium overload has been suggested to be involved in electrical remodeling largely on the basis of indirect evidence using L-type Ca-channel antagonists. 2,10 Mitochondrial Ca accumulation has been implicated in the process of electrical remodeling because mitochondria can buffer large increases in intracellular Ca when cytoplasmic free Ca reaches pathologically high (micromolar) levels. 7 However, under physiological conditions, total mitochondrial Ca is low (Ͻ1 mmol/kg dry wt) and does not increase significantly during systole, 11 despite a Ca transient of approximately 500 to 600 nmol/L.…”
mentioning
confidence: 99%
“…Tieleman et al demonstrated in a goat model that the shortening of the AERP caused by rapid atrial pacing was significantly attenuated by verapamil, but only during short-term pacing. 7 Several studies have similarly reported that verapamil might suppress the shortening of AERP in the relatively short term (<24 h). 1,11,12,15 Lee et al demonstrated that verapamil did not suppress the shortening of AERP in a relatively long-term model (1 and 6 weeks), although they did not evaluate the progression of the atrial electrical remodeling.…”
Section: Effect Of Antiarrhythmic Drugs On Atrial Electrical Remodelingmentioning
confidence: 98%
“…Atrial electrical remodeling has been evaluated in several animal models of rapid atrial pacing, 1,2,4,7,9,10,[20][21][22][23] which have documented the shortening of the AERP and prolongation in atrial conduction time, but few have reported the inhomogeneity in the process of atrial electrical remodeling. We previously reported that the shortening of the AERP was larger at the RAA and LA sites than at the other atrial sites when the rapid pacing was performed from the RAA site for 2 weeks.…”
Section: Inhomogeneity Of Electrical Remodelingmentioning
confidence: 99%
See 1 more Smart Citation